Acap model and innovation in U-I relationship - Engelman, Raquel; Schreiber, Dusan (Contextus - Revista Contemporânea de Economia e Gestão, 2018)
The purpose of this study is to see how the relationship between universities and companies influences the latter’s absorptive capacity and therefore competitiveness. The work focused on multiple-case studies with three companies based at the technology incubator of Feevale, a university center in Brazil’s south. Data analysis was based on Zahra and George’s (2002) ACAP model. Both diversity of search forms and harnessing new knowledge showed to be crucial in distinguishing those companies from others in the same sector. It is supposed that not only the university-business relationship may influence all businesses’ absorptive capacity and competitiveness but also achieving and sustaining competitive advantage is directly related to realized ACAP through innovation and product development as well as to potential ACAP through flexibility in reconfiguring basic resources. The ACAP model was very useful for analyzing the ability to acquire knowledge and turn it into innovation.